Synthesis and Characterization of Hybridfiber from Gelatin Modified by PVACOS Using Coaxial Electrospinning Techniques as an Advanced Medical Textile Material - Siti Fatimah; Sarto Sarto; Moh. Fahrurrozi; Budhijanto Budhijanto (Emerging Science Journal, 2024)
The synthesis of hybrid fiber based on bovine bone gelatin combined with polyvinyl alcohol-chitosan-oxidized sucrose (PVACOS) has been successfully carried out using the coaxial electrospinning technique. The presence of oxidized sucrose can improve the diameter and the tensile strength of hybrid fibers due to the formation of new covalent bonds. The combination of gelatin with PVACOS material aims to increase the strength of the hybrid fiber so that it has better tensile strength characteristics and improves the diameter of the resulting hybrid fiber. The characterization of the resulting material was tested using FTIR, SEM, EDX, XRD, and TGA. Based on FTIR analysis, there is an increase in absorption intensity in the 2900 cm-1 – 3000 cm-1 band, which indicates the occurrence of covalent bond interactions so that it can increase the bond strength between materials with the performance of crystalline materials. Apart from that, the morphological structure of the hybrid fibers was also investigated using scanning electron microscopy (SEM), and the resulting fiber diameter for Ge-Ch, Ge-Ch-PVA, Ge-PVACOS 3%, and Ge-PVACOS 5%, respectively, was 0.4049 µm. 0.3735 µm, 0.3388 µm, and 0.3206 µm. The tensile strengths of hybrid fiber for Ge-PVACOS 3% and Ge-PVACOS 5%, respectively, are 39.91935 N/m2 and 76.12507 N/m2. Statistical tests show that the concentration of oxidized sucrose has a significant influence on hybrid fiber performance. The significance values for diameter and tensile strength are 0.0486 and 0.0325, respectively. According to this performance, the Ge-PVACOS hybrid fiber is recommended as a material for advanced medical textiles. Doi: 10.28991/ESJ-2024-08-02-022 Full Text: PDF